Analisis Pengaruh Investasi Swasta dan Pengeluaran Pemerintah Daerah Terhadap Pertumbuhan Ekonomi dan Kemiskinan di Provinsi Jambi - Siti Aminah (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2016)
This study aimed to analyze the effect of private investment and local government spending to economic growth and poverty in Jambi Province. Research using time series data from 1985 to 2012 year. The analytical tool used is regression by the method of "Ordinary Least Squares" (OLS). The findings of this study show that private investment and local government spending made a positive impact on economic growth Jambi Province.